Exclusive Breastfeeding with the Incidence of Stunting - Nani, Nasriani; Samiun, Zulfia; Nur, Muhammad Purqan (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Stunting is one of the disorders in the growth of children affected by poor nutrition and the occurrence of recurrent infections, especially during the critical first two years of life. According to the WHO, a child is classified as stunting when his or her height relative to age exceeds the deviation standard based on the child's growth standard. The aim of this study is to identify a correlation between exclusive breastfeeding and the possibility of stunting in 12 to 60-month-old children in the Mangasa Puskesmas Working Region of Makassar City. This type of research is quantitative analytics using case control designs with a retrospective approach. The subjects in this study were 70 newspapers, consisting of 35 stunting as a treatment group (intervention) and 35 non-stopping as a control group. Univariate and bivariate analysis using chi-square tests. The results of the analyses showed that the newborn who received only milk (exclusive) but with a stunting category of 15 newborns (42,9%), while the newcomer who did not give milk exclusively and suffered stunting as much as 20 newcomers (57,1%). The result of the bivariate analysis shows that there is a correlation (relation) between giving milk only (exclusive) and the stunting condition (p-value=0,030). Research shows the need to provide education to improve mothers’ knowledge, especially in preparation for the first 1,000 days of life.